Race to the Center : Competition for the Nikkei 225 Futures Trade - Ito, Takatoshi (IMF Working Papers; Working Paper, 1996)
This paper examines the impact of changes in margin requirements on returns, transaction volumes, and price volatility of Nikkei 225 futures on the Osaka Securities Exchange (OSE) and the Singapore International Monetary Exchange (SIMEX). An increase in margin requirement on one exchange is shown to reduce trading volume in the implementing exchange and to shift trade to the competing exchange. Price volatility or returns are not systematically affected by changes in margin requirements. The loss of OSE's market share of Nikkei futures trade is partly due to the increased transactions costs (relative to SIMEX), including the margin requirement.